Frequency of diminazene - resistant trypanosomes in populations of Trypanosoma congolense arising in infected animals following treatment with diminazene aceturate - Mamman, M.; Gettinby, N.B.; Murphy, N.B.; Kemei, S.; Peregrine, A.S. (American Society for Microbiology, 1995)
The frequency of trypanosomes resistant to diminazene aceturate at a dose of 26 mg/kg of bwt was investigated for populations of Trypanosoma congolense IL 3274 which reappeared in infected mice after intraperitoneal treatment with diminazene aceturate at the same dosage. At inoculum sizes of 102, 103, 104, 105, and 106 trypanosomes per mouse, the relapse populations were used to initiate infections in 5 groups of 100 mice each by the intravenous route. Immediately after infection, 50 mice in each group were treated intraperitoneally with diminazene aceturate at the aforementioned dosage; the other 50 mice functioned as untreated controls. Thereafter, all animals were monitored for 100 days for the presence of trypanosomes. In each group, trypanosomes were detected in 50 of 50 control mice, indicating 100% infectivity for all 5 inoculum sizes. In contrast, in the groups of 50 mice infected with 102, 103, 104, 105 and 106 trypanosomes and treated with diminazene aceturate, trypanosomes were detected in 4, 11, 13, 28, and 39 of 50 mice, respectively. By logistic regression, a good fit was found between the number of mice identified as parasitaemic and the inoculum sizes. Maximum likelihood estimates for the proportions of trypanosomes resistant to diminazene aceturate at 25 mg/kg of bwt for the inoculum of 102, 103, 104, 105, and 106 organisms were 8.335 X 10-4, 2.485 X 10-4, 3.02 X 10-5, 8.3 X 10-6, and 1.6 X 10-6, respectively. These findings indicate that the majority of the relapse trypanosomes were susceptible to the drug dosage used for selecting the population and that, surprisingly, the calculated proportion of organisms which survived drug exposure varied inversely with the inoculum size. Further experiments with mice indicated that the inverse relationship did not result from alterations in the pharmacokinetics of the drug with different inoculum sizes. The data therefore suggest that parasite inoculum size and drug dosage are important factors in estimating the apparent frequency of diminazene-resistant trypanosomes in populations of T. congolense occurring in vivo.